The effects of expectations-based monetary policy on international stock markets: An application of heterogeneous agent model - Hung, Kuo-Che; Ma, Tai (International review of economics & finance, 2017)
This study develops an empirical approach to measuring the monetary policy effectiveness for price stability based on stock market expectations. First, we use the fraction of fundamentalists estimated by the model of heterogeneous agents as an indicator of agents' predictions of stock market movements. When the expectations of fundamentalists are the only basis for interest rate policy decision making, our results in seven countries show that those with an overvalued stock price use tight monetary policy so than the price falls to the fundamental level, and countries with an undervalued stock price use expansionary monetary policy so the price increases to the fundamental level. Furthermore, the stock price in the next six months in these countries continues to show a negative reaction to expectations-based monetary policy. In addition, in countries not subject to the influence of monetary policy based on the expectations of fundamentalists, our survey results showed that within the next three months, in more than 33% of cases, stock prices reacted negatively to policy. In short, the effect of expectations-based interest rate policy on price stability is superior to adjustments in the policy rate by monetary policy committees. Our results remain robust following a series of additional tests. •We develop an empirical approach to measuring the monetary policy effectiveness for price stability based on stock market expectations.•This study was carried out between January 1996 and December 2011, covering monthly data from ten countries.•The effect of expectations-based interest rate policy on price stability is superior to adjustments in the policy rate by monetary policy committees.•Stock price still had negative responses to expectations-based monetary policy over the next six months.